8.0k views
3 votes
Rewrite the expression as a sum of terms, where each term is in the form k\cdot a^nk⋅a

n
k, dot, a, start superscript, n, end superscript.
\sqrt a\left(2a^2-\dfrac4a\right)=
a
​ (2a
2

a
4
​ )=

User Realkes
by
5.3k points

1 Answer

1 vote

Answer:


2a^{(5)/(2)}-4a^{-(1)/(2)}

Explanation:

It looks like you want to expand the expression ...


√(a)\left(2a^2 -(4)/(a)\right)

Use the distributive property and rules of exponents.


=2a^{((1)/(2)+2)}-4a^{((1)/(2)-1)}\\\\=\boxed{2a^{(5)/(2)}-4a^{-(1)/(2)}}

_____

The relevant rules of exponents are ...

√a = a^(1/2)

1/a = a^-1

(a^b)(a^c) = a^(b+c)

User Maryann
by
5.7k points